A Comprehensive Pedagogical Framework for Teaching IoS App Design Course - Lokare, Varsha T.; Jadhav, Prakash M. (Journal of Engineering Education Transformations, 2025)
In modern education, equipping students with the skills and expertise to navigate the dynamic landscape of iOS app design demands a pedagogical approach that merges cutting-edge technologies with effective instructional strategies. This paper introduces a comprehensive pedagogical framework that combines the power of Visily AI, the interactive environment of Replit, and the project-based learning (PBL) approach to enhance the teaching of iOS app design. By synergizing these components, we create an immersive learning experience that caters to diverse learning styles, fosters collaboration and cultivates practical skill acquisition. Our study delves into the distinctive attributes of each tool, the theoretical underpinnings of their effectiveness, and their collective impact on student engagement and learning outcomes. Through case studies and practical implementation in an iOS app design course, we demonstrate how Visily AI aids in visual recognition tasks, Replit empowers students with a responsive coding environment, and PBL fosters real-world application and problem-solving skills. By amalgamating these elements, educators can bridge the gap between theoretical knowledge and practical proficiency. The outcomes of our approach are evidenced through improved student performance, increased motivation, and enhanced critical thinking abilities. This paper provides insights for educators seeking to enrich their iOS app design courses by harnessing the potential of Visily AI, Replit, and PBL. Ultimately, our comprehensive pedagogical framework facilitates technical competence and nurtures innovation, collaboration, and adaptability—qualities essential for success in the evolving landscape of iOS app design.